1986
DOI: 10.1002/j.1460-2075.1986.tb04254.x
|View full text |Cite
|
Sign up to set email alerts
|

Variable DNA splicing sites of a mitochondrial intron: relationship to the senescence process in Podospora

Abstract: The unavoidable phenomenon of senescence in Podospora was previously shown to be correlated with the presence of a senescence‐specific DNA originating from amplification of some regions of the mitochondrial chromosome. The most frequently amplified region (α) corresponds to the first intron of the gene coding for subunit one of cytochrome oxidase. Eleven long‐lived mitochondrial mutants were isolated. Here we report sequencing experiments that show that three of them are deleted for most of intron α and for a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0
1

Year Published

1986
1986
1999
1999

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(18 citation statements)
references
References 25 publications
1
16
0
1
Order By: Relevance
“…3). This explains the phenotype of the revertant mycelium in most points similar to that of other mitochondrial mutants of Podospora, which were shown to have a part of the CO] gene deleted (16,18). More interestingly, the reversion of the premature death phenotype is correlated with loss of the wild-type upstream exon-intron a junction, which is one of the target sequences for the deletion.…”
supporting
confidence: 57%
See 2 more Smart Citations
“…3). This explains the phenotype of the revertant mycelium in most points similar to that of other mitochondrial mutants of Podospora, which were shown to have a part of the CO] gene deleted (16,18). More interestingly, the reversion of the premature death phenotype is correlated with loss of the wild-type upstream exon-intron a junction, which is one of the target sequences for the deletion.…”
supporting
confidence: 57%
“…Preparation, purification, cloning, restriction analyses, and DNADNA hybridization of mtDNA were done by standard methods as described (9,16,18 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown by others that independent nuclear mutations, each with moderate effects on longevity, can act synergistically to produce strains with markedly increased longevities (8). It has also been demonstrated that mitochondrial rearrangements, many of which include the region from which a senDNA is derived, can significantly increase longevity (2,7,13). Therefore, the TS1 mutant may contain more than one genetic alteration, and it is possible that the continuousgrowth phenotype is separable from the temperaturesensitive phenotype.…”
Section: Resultsmentioning
confidence: 99%
“…A number of observations have supported this hypothesis. Several long-lived mutant strains, isolated as outgrowths from senescent mycelia of the s race, have been reported to lack the mitochondrial sequence from which a senDNA is derived (2,7,13). Furthermore, a subset of these mutants lack the freely replicating plasmid (26,27), as does a double nuclear mutant gr viv (23).…”
mentioning
confidence: 99%